THE ENHANCEMENT OF STUDENTS LEARNING PROCESS OF CHEMICAL BOND THROUGH DISCOVERY-BASED COOPERATIVE LEARNING - Fahmi, Fahmi (Unnes Science Education Journal, 2018)
Learning activity is an objective of learning process as wellas the indicator of success for students’ future understanding. Learning activity can be observed during the learning process. This research intends to enhance students’ learning activity through discovery-based cooperative learning. This action research was done in 2 cycles, with 2 meetings in each cycle. The subject of the research is the learning activity of students in X MIPA-7 SMA Negeri 1 Pekalongan, 1st semester, academic year 2016-2017. The result of the research showed that students learimproved 19% starting from 73% (good) in cycle 1 to 92% (very good) in cycle 2 with very good success indicator. The improvement shows that discovery-based cooperative learning can improve students’ learning activity. Other result also showed that there is an improvement of behavior in very good category.